Inhibition of Acute Graft-versus-Host Disease with Retention of Graft-versus-Tumor Effects by Dimethyl Fumarate - Han, Jingjing; Ma, Shoubao; Gong, Huanle; Liu, Shuangzhu; Lei, Lei; Hu, Bo; Xu, Yang; Liu, Haiyan; Wu, Depei (Frontiers in Immunology, 2017)
Acute graft-versus-host disease (aGVHD) remains a clinical challenge and a major source of morbidity and mortality following allogeneic hematopoietic stem cell transplantation (allo-HSCT). Dimethyl fumarate (DMF), an activator of Nrf2, has been shown to have anti-inflammatory and immunomodulatory properties without significant immunosuppression. We therefore hypothesized that DMF could be potentially harnessed for the treatment of aGVHD with retention of graft-versus-tumor effect. In this study, we showed that DMF significantly inhibited alloreactive T cell responses in vitro in mixed lymphocyte reaction assay. Administration of DMF significantly alleviated the severity, histological damage, and the overall mortality of aGVHD in an MHC-mismatched aGVHD model. DMF administration reduced the activation and effector function of donor T cells in vitro and in vivo. In addition, DMF treatment upregulated antioxidant enzymes heme oxygenase-1 and glutathione S-transferase-α1 expressions. Furthermore, DMF treatment markedly increased the frequencies of Treg cells. Depletion of CD25+ cells in DMF recipients aggravated aGVHD mortality compared with IgG control recipients. DMF could promote Treg cell differentiation in a dose dependent manner by upregulating TGF-β expression in vitro. Most importantly, DMF administration preserved graft-versus-leukemia effect after bone marrow transplantation. In conclusion, our findings demonstrated DMF as a promising agent for the prevention of aGVHD after allo-HSCT.